2006
DOI: 10.1007/s10858-006-9025-x
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state NMR spectroscopy of 10% 13C labeled ubiquitin: spectral simplification and stereospecific assignment of isopropyl groups

Abstract: We describe the simplification of 13C-13C correlation spectra obtained from a microcrystalline protein sample expressed on a growth medium of 10% fully 13C labeled glucose diluted in 90% natural abundance glucose as compared to a fully labeled sample. Such a labeling scheme facilitates the backbone and side-chain resonance assignment of Phe, Tyr, His, Asp, Asn, Ile, Lys and Pro and yields an unambiguous stereospecific assignment of the valine Cgamma1, Cgamma2 13C resonances and of Leucine Cdelta2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…The last six C-terminal residues cannot be assigned due to dynamic disorder. In previous studies of MPD-crystallized ubiquitin by ssNMR, only a single set of resonances was reported (Igumenova et al 2004;Schubert et al 2006). One of the reasons for this may lie in the slightly different crystallization conditions used.…”
Section: Design Of Bsh-cp Based 3d Pulse Schemesmentioning
confidence: 99%
“…The last six C-terminal residues cannot be assigned due to dynamic disorder. In previous studies of MPD-crystallized ubiquitin by ssNMR, only a single set of resonances was reported (Igumenova et al 2004;Schubert et al 2006). One of the reasons for this may lie in the slightly different crystallization conditions used.…”
Section: Design Of Bsh-cp Based 3d Pulse Schemesmentioning
confidence: 99%
“…In these cases, a bacterial culture is grown up in the absence of protein overexpression, cellular RNA or DNA is isolated and hydrolyzed to monomeric units, the resulting monomers are rephosphorylated to nucleoside triphosphates (NTPs), and the ribo-or deoxyribo-NTPs are used as feedstocks for in vitro enzymatic synthesis of the sequence of interest (8,9). (For purposes of uniform labeling, 15 N-and 13 C, 15 N-NTPs have recently become commercially available, although at considerable expense). Although this procedure is more involved than that for proteins, it is in some senses more general for the schemes described in this review, since transformation and overexpression in a mutant strain is unnecessary.…”
Section: Applications Of Metabolic Labelingmentioning
confidence: 99%
“…Statistical labeling has also found use in a number of other contexts, including spectral simplification in solid-state NMR (15) and as an aid to residue type identification to facilitate backbone-directed resonance assignment (16). In a preliminary application to nucleic acids, Kishore et al (17) have used a mixture of C-1 and C-2 labeled glucose as a feedstock for E. coli and found some useful labeling patterns in the resulting ribonucleosides, including a high level of enrichment at ribose C1 0 .…”
Section: Statistical Labeling For Stereospecific Assignmentsmentioning
confidence: 99%
See 2 more Smart Citations